Factor that can contribute to application of electronic tax filing among Malaysian taxpayers : a perception of UTM accounting students [electronic resource] - Syahira Zulmahdi, 1992-; Norkhairul Hafiz Bajuri; Fakulti Pengurusan (2015)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2015